1991
DOI: 10.1080/00071669108417428
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of growth curves of fowl. II. Ducks

Abstract: 1. Growth curves of nine selected lines and one random-bred control population (in total, n = 1070) were evaluated by the Richards function. The ducks were weighed at 7-d intervals and, after the tenth week, every second week (up to 18 weeks). Food and water were supplied ad libitum. 2. The predicted curves closely fitted the weight data points (R2 = 0.9991-0.9997). 3. The ducks are characterized by early maturity rate. The peak of the absolute growth rate (the inflection point of the curve) occurred at 24.1-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The present study supports the work of Knízetová et al (1991a), who compared the same 3 nonlinear functions and concluded that the Richards function is best for growth analyses of ducks and other poultry, such as geese and chickens. Yang et al (2006) compared the fit of logistic, Gompertz, and Bertalanffy curves to experimental growth data of Jinghai mixed-sex yellow chickens, and they found the Bertalanfly model to give the best approximation to experimental data.…”
Section: Discussionsupporting
confidence: 92%
“…The present study supports the work of Knízetová et al (1991a), who compared the same 3 nonlinear functions and concluded that the Richards function is best for growth analyses of ducks and other poultry, such as geese and chickens. Yang et al (2006) compared the fit of logistic, Gompertz, and Bertalanffy curves to experimental growth data of Jinghai mixed-sex yellow chickens, and they found the Bertalanfly model to give the best approximation to experimental data.…”
Section: Discussionsupporting
confidence: 92%
“…The growth rate of ducks and geese is fast at the early stages of life, and then it slows down (Knízetová et al, 1991). Broiler chickens grow more slowly than ducks and geese in the first few week of their life and faster in the subsequent week.…”
Section: Discussionmentioning
confidence: 97%
“…In both models, weight of bending point (POI = point of inflection) is determined as (y +=5560 g) and age (t+=11.9 day), and bending/asymptotic weight ratio is determined as (y+/A=0.368), during 16th and 18th weeks maturity degree (ut = yt/A, degree of maturity), is determined respectively similar as: 0549 and 0627. Knizetova, et al [13][14][15], in their study using the Richards model, bending/asymptotic weight ratio (y+/A) estimated between 0.370 to 0.388 for broilers, 0.380 to 0.424 for ducks and 0.233 to 0.294 for geese.…”
Section: Resultsmentioning
confidence: 99%
“…In their application of Logistic and Gompertz model on broilers fed ad libitum Stephan, et al [18] calculated, the values of R2, respectively, at the level of 0.979 and 0.980 and similar to the actual values. In their application of Richards model on broiler chicks, ducks and geese, Knizetova, et al [13][14][15], calculated the values of R2 respectively between 0.9986-0.9995, 0.9994-0.9901. In their application of Richards model on White, Brown and wild male Japanese quail [19], estimate the values of R2 as 0.9996-0.997 in males and as 0.9986-0.9991 in females.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation